Circulating soluble P-selectin must dimerize to promote inflammation and coagulation in mice - Panicker, Sumith R. (Blood, 2017)
Leukocyte adhesion to P-selectin on activated platelets and endothelial cells induces shedding of the P-selectin ectodomain into the circulation. Plasma soluble P-selectin (sP-selectin) is elevated threefold to fourfold in patients with cardiovascular disease. Circulating sP-selectin is thought to trigger signaling in leukocytes that directly contributes to inflammation and thrombosis. However, sP-selectin likely circulates as a monomer, and in vitro studies suggest that sP-selectin must dimerize to induce signaling in leukocytes. To address this discrepancy, we expressed the entire ectodomain of mouse P-selectin as a monomer (sP-selectin) or as a disulfide-linked dimer fused to the Fc portion of mouse immunoglobulin G (sP-selectin-Fc). Dimeric sP-selectin-Fc, but not monomeric sP-selectin, triggered integrin-dependent adhesion of mouse leukocytes in vitro. Antibody-induced oligomerization of sP-selectin or sP-selectin-Fc was required to trigger formation of neutrophil extracellular traps. Injecting sP-selectin-Fc, but not sP-selectin, into mice augmented integrin-dependent adhesion of neutrophils in venules, generated tissue factor–bearing microparticles, shortened plasma-clotting times, and increased thrombus frequency in the inferior vena cava. Furthermore, transgenic mice that overexpressed monomeric sP-selectin did not exhibit increased inflammation or thrombosis. We conclude that elevated plasma sP-selectin is a consequence rather than a cause of cardiovascular disease.